2022
DOI: 10.3390/w14010123
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Azo Dyes with Different Functional Groups in Simulated Wastewater by Electrocoagulation

Abstract: Increasing attention has been paid to the widespread contamination of azo dyes in water bodies globally. These chemicals can present high toxicity, possibly causing severe irritation of the respiratory tract and even carcinogenic effects. The present study focuses on the periodically reverse electrocoagulation (PREC) treatment of two typical azo dyes with different functional groups, involving methyl orange (MO) and alizarin yellow (AY), using Fe-Fe electrodes. Based upon the comparative analysis of three main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Te electrocoagulation process investigated by Lach et al [84] revealed a high azo dye removal efciency (96.5%) with TOC and COD of 93.5% and 85.0%, respectively. Liu et al [85] presented a reverse electrocoagulation treatment of methyl orange and alizarin yellow dyes using Fe-Fe electrodes. Te efciency for methyl orange and alizarin yellow achieved was 98.7% and 98.6%, respectively, using NaCl as the electrolyte.…”
Section: Electrocoagulation Te Electrocoagulation Techniquementioning
confidence: 99%
“…Te electrocoagulation process investigated by Lach et al [84] revealed a high azo dye removal efciency (96.5%) with TOC and COD of 93.5% and 85.0%, respectively. Liu et al [85] presented a reverse electrocoagulation treatment of methyl orange and alizarin yellow dyes using Fe-Fe electrodes. Te efciency for methyl orange and alizarin yellow achieved was 98.7% and 98.6%, respectively, using NaCl as the electrolyte.…”
Section: Electrocoagulation Te Electrocoagulation Techniquementioning
confidence: 99%
“…Dyes show negative impacts on both the surface water and groundwater quality by blocking light transmission, affecting the photosynthesis of aquatic flora and by reducing dissolved oxygen in water [131]. Dyes are toxic to aquatic ecosystem and human beings due to its mutagenic, carcinogenic and genotoxic nature [132,133]. Many technologies have been applied for the treatment of wastewater such as electrochemical methods, reverse osmosis, ozone oxidation, chemical precipitation, membrane separation, adsorption and photocatalysis etc.…”
Section: Environmental Applicationsmentioning
confidence: 99%
“…Organic dyes inhibit light penetration through water, slow down photosynthesis reactions, hinder sunlight penetration, lower photosynthesis activity, and cause oxygen defcit, all of which have an impact on water quality. Furthermore, certain chemical dyes like azo dyes can cause mutagenic and carcinogenic efects [4]. Synthetic dyes, which are used in large quantities in the textile industry, are chemically stable and harmful to the environment.…”
Section: Introductionmentioning
confidence: 99%